Psychiatric nurses' experience of aggression amongst colleagues - Marisa Delport; Marie Poggenpoel; Chris Myburgh (AOSIS, 2018)
Psychiatric nurses run a high risk of being exposed to aggression. They experience aggression from clients as well as fellow colleagues. Aggression in the work environment has an overt negative psychological effect on the nurse. The purpose of this research was to explore and describe how psychiatric nurses experienced aggression amongst colleagues in the work environment. The study used a qualitative, exploratory and descriptive research design. Eight psychiatric nurses exposed to aggression by their colleagues in an academic psychiatric hospital in Johannesburg were purposively sampled to participate in this study. Data were collected by means of in-depth phenomenological interviews, observations and field notes until data saturation was achieved. The following question was asked: 'What is your experience of aggression amongst colleagues in the work environment?'. The findings indicated that the psychiatric nurses experienced aggression in a passive but harmful manner. The nurses experienced a suspicious and distrustful team environment. Limited support was experienced when colleagues and management did not acknowledge aggression and the nurses applied various coping and defence mechanisms when emotional stress and aggression were experienced. The aggression psychiatric nurses experienced had an effect on their experience on self, team work and providing services to patients.